Search for resonant and nonresonant Higgs boson pair production in the b(b)over-barl nu l nu final state in proton-proton collisions at root s=13 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Ambrogi,F; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; et al. (JOURNAL OF HIGH ENERGY PHYSICS, 2018)
Searches for resonant and nonresonant pair-produced Higgs bosons (HH) decayingrespectively into `ν`ν, through either W or Z bosons, and bb are presented. The ¯analyses are based on a sample of proton-proton collisions at √s = 13 TeV, collected bythe CMS experiment at the LHC, corresponding to an integrated luminosity of 35.9 fb−1.Data and predictions from the standard model are in agreement within uncertainties. Forthe standard model HH hypothesis, the data exclude at 95% confidence level a product ofthe production cross section and branching fraction larger than 72 fb, corresponding to 79times the standard model prediction. Constraints are placed on different scenarios consideringanomalous couplings, which could affect the rate and kinematics of HH production.Upper limits at 95% confidence level are set on the production cross section of narrowwidthspin-0 and spin-2 particles decaying to Higgs boson pairs, the latter produced withminimal gravity-like coupling.